Understanding the market and access gaps present in South Africas broadband internet sector - Cameron, Alan (Department of Civil Engineering, 2017)
Internet access is a prerequisite for meaningful individual and national participation in the knowledge economy and removing barriers to such access serves broader national socio-economic policy imperatives. This critical review of the literature posed the questions: What is South Africa's current telecommunications context from a Universal Access and Universal Service point of view and does a market gap and/or access gap remain despite efforts to address such gaps since 1994? If so, how do either or both the market gap and access gap appear in the South African context and what are key hurdles that need to be overcome in order to close these gaps? The review provides a plain language explanation of how broadband Internet access can benefit South Africa's economy, and describes the negligible impact of existing policy in an anti-competitive market environment. A brief overview of South Africa's telecommunications history since 1994 until 2016 helps to contextualise the sector. In the early 1990s, 2% of South Africans had access to voice telephony. A few years later Universal Service and Access regulation was overtaken by the rapid adoption of mobile phones. With more than 40% voice telephony domestic penetration the network effect of quicker communication stimulated the domestic economy. Having achieved Universal Access objectives relating to voice communications, today nations seek the compounded advantages from the network effect of broadband Internet access. South Africa's GDP is predicted to grow by 1.34% for every 10% increase in broadband penetration, through increased productivity, job creation and greater access to cheaper services. However almost two thirds of South Africans cannot afford Internet access; and neither action by the free market nor the state is effectively increasing levels of cheap, accessible Internet. Incumbent service providers dominate the South African telecommunications sector and have little incentive to accelerate Internet access and adoption to low-income households and areas outside of the major metropolitan areas. It is therefore necessary that policy facilitates: competition in the ICT product and services sector, effective spectrum management, productive Internet use by lowincome households and user demand for online content.